DEVELOPING LANDING PAGES AS DIGITAL MARKETING TOOLS FOR MSME PRACTITIONERS IN CIGUGUR: AN EDUCATIONAL APPROACH - Surya Lesmana, Arief; Ganefi, Hadi Satria; Muttaqien, Dadan Darmawan (LPPM Univ. Ibn Khaldun Bogor, 2024)
Cigugur Village as one of the Tourism Village in Kuningan Regency has great potential to improve the economy of its community through MSMEs. Many local MSME products have advantages but are not supported by appropriate marketing strategies. The majority of MSMEs still apply conventional marketing by word of mouth and entrust it to retail stores. As a result, sales tend to stagnate and it is difficult to compete with competitors in the market. Therefore, this community service was carried out to provide education to Cigugur Village MSMEs regarding the latest digital marketing strategies by creating an integrated WhatsApp Business landing page by utilizing the free features of Canva. A total of 20 participants took part in this program. After this activity was carried out, the participants succeeded in creating a simple landing page quite well. After being provided with education, there was an increase in the participants’ understanding of digital marketing concepts and the practice of using them. It is hoped that this service activity can help MSME players develop their business through digital marketing tools, such as landing pages, thereby positively impacting the survival and sustainability of Cigugur Village MSMEs.